Kajian Etnobotani Tumbuhan Cangkuang (Pandanus furcatus Roxb.) di Masyarakat Adat Kampung Pulo Garut - Lida Amalia; Fitriani Dewi Sontani; Siti Nurkamilah (Journal Civics and Social Studies, 2021)
Ethnobotany Study of Cangkuang (Pandanus furcatus Roxb.) Plants in the Indigenous Peoples of Kampung Pulo Garut.  Aims to determine the ethnobotany of Cangkuang plants through several studies, and to find out the percentage of growth strata, parts of organs used, and their utilization. The benefit of this research is to provide information on ethnobotany from various aspects of the study and to inspire the community to cultivate Cangkuang. The research method uses descriptive qualitative method, the method of work is carried out directly in the field and supported by interview respondents (semi-structural and open ended). Determination of respondents and data collection of plant samples using purposive sampling method. Based on research, observation and interviews, the botanical study of Cangkuang plants has an elongated taper leaf morphology, thory edges, has tap roots, no flower shape found. Ethnopharmacology, leaves and fruit as a medicine for diarrhea, dysentery, and antioxidants. Ethnolinguistics, Cangkuang is used as the name of a village, lake, temple and tourist park. Ethnoanthropology, the fruit has a myth as a repellent for spirits. Ethnoeconomics, the leaves are useful as household tools and food wrappers. Percentage of growth stages, 68 % seedlings, 16 % saplings, 9 % poles, and 7 % trees. The percentage of plant parts used, leaves 83% and fruit 17%. Percentage of plant utilization, 50 % medicine, 30 % of food wrappers, 17 % household appliances, and 3 % mythical object.